Topology Optimisation of Engine Cross Members for Lightweight Structure in Light Commercial Vehicles - Hoke, Ozgun; Bozca, Mehmet (KOREAN SOC PRECISION ENG, 2020)
Topology and topography optimisations of engine cross members that were produced from sheet metal are presented. The Hyper Mesh, Opti-Struct, and Hyper-View tools in the Hyper Works software package, which is programmed by the Altair Company, were utilised in the analyses. For this purpose, two designs, software-based design optimisation (SBDOP) and expert-based design optimisation (EBDOP), were created using the trial-and-error method. The methods were compared and contrasted to the baseline in terms of the equivalent static and dynamic stiffness under both translational and rotational conditions and in terms of the linear stress distribution. In the final stage, the production design was created to conduct manufacturability analyses. Consequently, it was observed that with the use of optimisation software and tools, SBDOP can provide significant improvements in terms of time and functionality. Without violating the performance targets, such as the static and dynamic stiffness and stress distribution expected by the related OEM, the mass was reduced, and 12% improvements in weight were obtained.
Keywords: Topology optimisation; Topography optimisation; Static stiffness; Dynamic stiffness; Weight reduction; Engineering